Appreciating the Resilience and Stability Found in Heterogeneity: A South African Perspective on Urban Household Food Security - Nenguda, Rendani; Scholes, Mary Catherine (Frontiers in Sustainable Food Systems, 2022)
Urban food security has long been viewed as secondary to rural food security in Africa, and with the migration of large numbers of individuals from rural to urban settings, it has become crucial to place more focus on urban food security. More so, in Southern African peri-urban areas, where high unemployment rates amongst the youth exist. Often, the interventions toward reducing food insecurity in urban settings are taken from those previously designed for application in the rural context. In this study, we aimed to measure the status of food security and identify the factors driving and constraining household food security amongst peri-urban households in Tembisa, South Africa, with the purpose of gaining an in depth understanding of the drivers of urban food insecurity within peri-urban communities. In order to accomplish this, FANTA's Household Food Insecurity Access Scale (HFIAS), which measures levels of food security and the Household Dietary Diversity Scale (HDDS), which measures the level of nutritional intake of households was applied. Food prices of the formal and informal markets were monitored over a period of 6 months. A significant decline in household food access over a 4-year period (2013–2016) was observed in addition to low-quality diets. The most commonly used coping methods during periods of low income included borrowing either money or food from friends and neighbors, this was done in conjunction with various other coping strategies. Much of the declining food access was attributed to the inflation of food prices, the lack of employment, lack of formal employment and a high number of household members to breadwinner ratios. High reliance solely on financial capital remains a limitation to the livelihood of urban households. Informal markets are an imperative driver of food security in these peri-urban communities and provide improved food price stability, temporal, and geographical food access through less volatile food pricing, compared to formal markets. Furthermore, government initiatives such as social grants and school feeding schemes have proven to be critical in reducing the vulnerability to food insecurity of most households.